GENERACIÓN DE VENTAJA COMPETITIVA A TRAVÉS DEL DISEÑO DE ESTRATÉGIAS PARA LA INTEGRACIÓN DE LOS ACTORES DEL SECTOR TURÍSTICO EN LA PROVINCIA DE SUGAMUXI (2016)
This article aims to study center their strategies leading to the achievement of competitive advantages from the integration between the various stakeholders in order to maximize the territorial and cultural assets Sugamuxi province. It aims through an extensive literature review, establish the determinants to generate tourism development in the regions from which the present conditions of the sector in the Province of Sugamuxi be evaluated, all from the framework of the model “ Competitiveness Diamond “Porter, who established through their Monitor integration studies must be a determining factor in the rise and development of the sector and taking clear that in order to legitimize the Provincial Tourism Council to date has failed develop concrete actions seeking competitive advantages due to the lack of integration of actors in the sector in the province, it is conducive to establish the cluster model as a strategy to generate competitive advantage and therefore mark the future of the sector.